Kelimpahan Serangga Pada Berbagai Jenis Tumpangsari Kacang Kedelai Dengan Tanaman Refugia - Siti Syarah Maesyaroh; Jajang Supriatna (Faculty of Agriculture University of Singaperbangsa Karawang, 2021)
The study aims to determine the abundance of insects in various types of intercropping of soybean with refugia plants. The research was conducted at Kp. Rancabango Kec. Tarogong Kaler from May to November 2020. The method used in this research is descriptive quantitative method. The various kinds of intercropping treatment consisted of borders, mix cropping, refugia only and soybeans only. Based on the results of the study, it was shown that the index of diversity values of fitfall trap and yellow trap on the intercropping land of soybean with refugia plants were in the medium category and the dominance index value in the traps both were in the low category.